2020
DOI: 10.1088/1361-6501/ab8b83
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the pitch deviation of a linear scale based on a self-calibration method with a Fizeau interferometer

Abstract: A self-calibration method, in which the wavefronts of zeroth and first-order diffracted beams from a scale grating measured by a Fizeau interferometer are employed, is applied for the evaluation of the pitch deviation of a reflective-type linear scale with a grating pitch of 2.048 μm used in a commercial interferential scanning-type optical linear encoder. One of the advantages of the self-calibration method is that the pitch deviation of a scale grating can be evaluated while measuring the out-of-flatness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…It should be noted that the influence of the out-of-flatness of a grating under test can also be included in the observed phase shifts; it can be cancelled by the arithmetic operation with the wavefront data of the positive and negative first-order diffracted beams [37]. This arithmetic operation also gives the selfcalibration characteristic to the measurement since the influence of the out-of-flatness of the reference flat can also be removed [40].…”
Section: Evaluation Of the Wavefront Aberrations By Using A Fizeau In...mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the influence of the out-of-flatness of a grating under test can also be included in the observed phase shifts; it can be cancelled by the arithmetic operation with the wavefront data of the positive and negative first-order diffracted beams [37]. This arithmetic operation also gives the selfcalibration characteristic to the measurement since the influence of the out-of-flatness of the reference flat can also be removed [40].…”
Section: Evaluation Of the Wavefront Aberrations By Using A Fizeau In...mentioning
confidence: 99%
“…It should be noted that, in the method, the influence of the out-of-flatness error of the grating can be cancelled by the arithmetic operation with the wavefront data of the positive and negative diffracted beams [37]. A further investigation of the method has also revealed that the self-calibration of the out-of-flatness of the reference flat in a Fizeau interferometer can also be realized by using the wavefront data of the zeroth-and positive and negative firstorder diffracted beams [40]. Meanwhile, this method has not been applied to the evaluation of a VLS planar scale grating so far.…”
Section: Introductionmentioning
confidence: 99%
“…The authors’ group has proposed a self-calibration method, in which the pitch deviation of a standard grating can be evaluated while self-calibrating the out-of-flatness of the reference flat in a Fizeau interferometer. In the method, the pitch deviation of the grating can be readily evaluated by using the wavefronts of the first-order diffracted beams from a grating [ 24 , 25 ]. The self-calibration method has been further extended to evaluate the pitch distribution of a VLS grating by linking the VLS parameters with the differential wavefronts of the first-order diffracted beams through a simple polynomial fitting process [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In responding to the above issues, an interferometric calibration method has been proposed to evaluate the pitch deviation of the scale grating using a Fizeau form interferometer through wavefront analysis [16]. The proposed method is further improved to a self-calibration method so that the influence of the reference flat error in the Fizeau interferometer can be removed [17][18][19].…”
Section: Introductionmentioning
confidence: 99%